In-group favoritism and discrimination among multiple out-groups - Veronika Grimm; Verena Utikal; Lorenzo Valmasoni (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2015)
In this study, we investigate how and why people discriminate among different groups, including their own groups and multiple out-groups. In a laboratory experiment, we use dictator games for five groups to compare actual transfers to in-group and out-group agents with the respective beliefs held by dictators and recipients in these groups. We observe both in-group favoritism and discrimination among multiple out-groups. Individuals expect others to be in-group biased, as well as to be treated differently by different out-groups. Dictators' in-group favoritism is positively related to the degree of in-group favoritism they expect other dictators to exhibit. Moreover, we find that a dictator tends to be relatively more generous toward a specific out-group when he or she expects that dictators belonging to that out-group are generous toward members of his or her ingroup.
Keywords: C91; C92; D84; D01; D64; 330; discrimination; experiment; group identity; dictator game; beliefs